(untitled) (International Journal of Current Research in Physiology and Pharmacology, 2023)
Introduction: Ulcers are deep lesions penetrating through the entire thickness of the gastrointestinal tract (g.i.t) mucosa. It is believed that the Gastric ulcer develops due to an imbalance between aggressive factors (Helicobacter pylori, NSAIDs, Gastric acid) and protective factors (mucin, bicarbonate, prostaglandins), leading to the interruption in the mucosal integrity. Gastric ulcer, also known as peptic ulcer, is a localized area of erosion in the stomach lining, resulting in abdominal pain, possible bleeding and other gastrointestinal symptoms. The most common cause of gastric ulcer is a stomach infection associated with the Helicobacter pylori (H. pylori) bacteria. Current treatment and management of gastric ulcer disease include proton pump inhibitors, Ulcer protective agents, anti-histamines, anticholinergics, antacids, and anti-H.pylori drugs etc. Aim: The present study was designed to investigate the potential role of adenosine in indomethacin-induced gastric ulcers in Wistar rats. This study also aims to explore the role of purinergic receptors in gastric ulcers. Materials and method: Gastric ulcer was induced in Wistar rats (180-210g) of either sex by administration of indomethacin (5mg/kg, p.o., 14 days) and the animals were sacrificed, stomachs were removed for estimation of various parameters such as ulcer index, mucin percentage, percentage of inhibition of ulcer index, estimation of pH. Biochemical estimations such as MDA, GSH, SOD and MPO activity were performed. Results: Administration of indomethacin in Wistar rats leads to gastric ulcers by an increase in ulcer index, decrease in mucin percentage and decrease in pH. The biochemical parameters like MDA and MPO are found to increase in the indomethacin control group.GSH and SOD were found to decrease than in the normal control group. Now the administration of a test drug (adenosine) was found helpful in the treatment of gastric ulcers in Wistar rats by decreasing the ulcer index, increase in pH and increase in mucin percentage. The biochemical parameters MDA and MPO were found to decrease and increase in GSH and SOD when compared with the control group. Theophylline, an adenosine receptor antagonist, shows increased gastric ulceration compared to the control group. Thus, the present data demonstrated that adenosine benefits gastric ulcers. Also, the present data demonstrate purinergic receptors’ possible role in adenosine’s cytoprotective effect. Keywords: Ulcers, Wistar rats, adenosine, indomethacin